1988
DOI: 10.1056/nejm198808253190802
|View full text |Cite
|
Sign up to set email alerts
|

Difference between Endothelium-Dependent Relaxation in Arterial and in Venous Coronary Bypass Grafts

Abstract: Both the internal mammary artery and the saphenous vein are used to construct coronary-artery bypass grafts. We hypothesized that the release or production of endothelium-derived relaxing factor, which regulates blood flow and inhibits platelet function, may differ in venous and arterial grafts. We therefore studied endothelium-dependent relaxation in internal mammary arteries, internal mammary veins, and saphenous veins obtained from 58 patients undergoing coronary bypass surgery. Vascular rings with and with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
189
1
9

Year Published

1989
1989
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 505 publications
(205 citation statements)
references
References 30 publications
6
189
1
9
Order By: Relevance
“…This is consistent with the observation that venous NOS expression is less than that in arterial endothelium. 18 Mechanical stimuli have been shown to influence several aspects of endothelial function. The constant shear stress produced by unidirectional flow maintains normal endothelial NOS protein (eNOS) expression by activation of the tyrosine kinase c-Src, which then leads to divergent pathways modulating both eNOS transcription rate and also its mRNA stability.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the observation that venous NOS expression is less than that in arterial endothelium. 18 Mechanical stimuli have been shown to influence several aspects of endothelial function. The constant shear stress produced by unidirectional flow maintains normal endothelial NOS protein (eNOS) expression by activation of the tyrosine kinase c-Src, which then leads to divergent pathways modulating both eNOS transcription rate and also its mRNA stability.…”
Section: Discussionmentioning
confidence: 99%
“…First, intravenous infusion of acetylsalicylic acid to inhibit the production of vascular prostaglandins4, [8][9][10][11]24 did not affect the increase in forearm blood flow observed during the infusion of the muscarinic agonist. Thus, a significant contribution of vascular prostaglandins to the vasodilator actions of acetylcholine in the human forearm in vivo can be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Similar conclusions have been reached in isolated blood vessels of experimental animals and of humans. [4][5][6][7][8][9][10][11] Second, an inhibition of adrenergic neurotransmission by acetylcholine-activating prejunctional muscarinic receptors has long been considered the main mechanism mediating the vascular effects of the 13 To exclude a contribution of prejunctional effects of acetylcholine, we compared the vasodilator action of the cholinergic neurotransmitter in the presence and absence of phentolamine to block postjunctional a-adrenergic receptors. Phentolamine alone increased blood flow, indicating effective blockade of a-adrenergic receptors in the forearm circulation.2025-27 Previous studies have shown that under these conditions, the effects of exogenous norepinephrine are inhibited.25 Thus, the effects of neurally released norepinephrine should be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Estes fatos, aliados aos estudos que mostram a importância da função das células endoteliais, como os de LÜSCHER et alii 16, onde se percebe que o endotélio arterial é mais reativo e protetor do que o venoso, fornecem um substrato científico muito forte para a utilização das mamárias na cirurgia das coronárias.…”
Section: Discussionunclassified